Economic analysis of oil palm smallholders in FELCRA Seri Mendapat, Merlimau, Melaka / Nur Asyiqin Zainol - Zainol, Nur Asyiqin (Faculty of Plantation and Agrotechnology, 2019)
Economic analysis refers to the opportunity costs of resources employed and attempts to measure in monetary term the private and social costs and benefits of a project to the economy. The Malaysian Oil Palm Industry is facing rising production cost which is partly due to stagnation in productivity and this affect business profitability. The purpose of this study is to examine the economic cost and benefit of oil palm smallholder as well as to determine the relationship of mutual influences between all the factors of land size, labour, production capital, plant age and identify the most significant factor affecting the profitability. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 25 and Microsoft Excel 2016. The data obtained were then analyzed using the benefit-cost ratio, descriptive statistic, correlation and multiple regressions. The results revealed during this study indicate that for the organized smallholder, the total cost is higher than independent smallholder (RM 1328.78 compared to RM 1279.60). For the profitability, independent smallholder gets higher profit than organized smallholder (RM 1399.03 compared to RM 1080.54). The result of the study also revealed that all four factors have positive relationships with the profit for organized smallholder and for independent smallholder it indicates three factors have positive relationships while another one factor (plant age) has negative relationship with profit. The multiple regression analysis indicated that for the organized smallholder, production capital and land size were the most salient determinants of profit while for independent smallholder, labour was the most salient determinant of profit. As such, it is hoped that this study will give a preliminary insight and understanding to organized and independent smallholder in order to achieve high yield and profit.